Are Immigrants Particularly Entrepreneurial? Policy Lessons from a Selective Immigration System - David A. Green; Huju Liu; Yuri Ostrovsky; Garnett Picot (Institute of Labor Economics (IZA), 2023)
Firm ownership is a dening feature of immigrant adaptation: 41% of immigrants own a firm at some point in their first 10 years post-arrival. We use Canadian data linking immigrant arrival records with individual and firm tax data to examine the process of entering firm ownership for immigrants. Higher immigrant firm ownership rates are mainly due to nonincorporated firm ownership, which looks like a last resort. Human capital plays no role in the opening of preferable, incorporated firms. Immigrants are not more entrepreneurial in terms of opening incorporated firms with employees, and standard policy levers appear to have limited effects.
Keywords: J61; 330; immigration; entrepreneurs; human capital